2016
DOI: 10.1002/jaal.585
|View full text |Cite
|
Sign up to set email alerts
|

Blurring Boundaries: Drama as a Critical Multimodal Literacy for Examining 17th‐Century Witch Hunts

Abstract: This article illustrates how critical multimodal literacy practices engage secondary students to further explore differences and similarities between past and present instances of discrimination within a process drama, where students and teachers explore a topic through unscripted role‐play. Data from a classroom‐based ethnography are drawn on to show how students in two grade 9 social studies classes made meaning from their engagements with a process drama about 17th‐century witch hunts. The authors use field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…Second, role‐play was methodologically aligned with both the theoretical framing of the project and our overall approach to the class. It provided students the opportunity to draw on their own translanguaging and served as one of many critical multimodal literacy practices (Schroeter & Wager, ) that students drew on to articulate their understandings of and talk back to raciolinguistic ideologies.…”
Section: Grappling With the White Listening Subject: Role‐play To Permentioning
confidence: 99%
See 1 more Smart Citation
“…Second, role‐play was methodologically aligned with both the theoretical framing of the project and our overall approach to the class. It provided students the opportunity to draw on their own translanguaging and served as one of many critical multimodal literacy practices (Schroeter & Wager, ) that students drew on to articulate their understandings of and talk back to raciolinguistic ideologies.…”
Section: Grappling With the White Listening Subject: Role‐play To Permentioning
confidence: 99%
“…Ms. Winter and I were “sensitive [to the] nature of students’ stories and the complex social dynamics at play in secondary schools” (Schroeter & Wager, , p. 411) and never directed the content of these role‐plays. To further ensure that students were not made uncomfortable, we often had students reflect on the role‐plays—both those they created and those they observed—privately in journals, rather than in whole‐group conversation (Schroeter & Wager, ).…”
Section: Grappling With the White Listening Subject: Role‐play To Permentioning
confidence: 99%
“…A study in an urban Toronto high school for adults featured immigrant English language learners from four continents engaging with classroom drama and found students benefited from creating multimodal drama work that symbolized critical issues in their lives, including political, social, and economic conditions (Ntelioglou, 2011). In a study of secondary history students examining 17th-century witch hunts in the US, Schroeter and Wager (2017) found that drama enabled students to link historical discrimination with parallel events in current times, including discrimination students had "experienced, witnessed, or participated in, such as racism, classism, homophobia, and bullying" (p. 406). The authors argue that physical enactment and use of the senses enabled students to enter history and reflect on it critically.…”
Section: Relating Social Justice Concepts To K-16 Classroom Dramamentioning
confidence: 99%
“…The use of drama pedagogy through a multiliteracy lens fosters students' critical linkage between past and contemporary issues that affect them directly (Ntelioglou, 2011;Perry & Medina, 2018). Schroeter and Wager (2017) add that critical multimodal literacy practices: are useful for contending with an increasingly diverse society, amid a climate of divisive identity politics and discriminatory policies […] Engaging students' multiple senses by employing different modalities through drama is thus one way that educators can help students step into an imagined history and critically reflect on it in ways that are relevant to them (p. 412).…”
Section: Relating Social Justice Concepts To K-16 Classroom Dramamentioning
confidence: 99%
“…Το υλικό αυτό μπορεί να περιλαμβάνει εικονογραφημένα [72] βιβλία (Roche, 2014), κόμιξ (Vie & Dieterle, 2016), γελοιογραφίες με πολιτικό περιεχόμενο (Wawra, 2018) και άλλες εικόνες (Albers, Vasquez & Harste, 2015). Μπορεί, ακόμη, ο κριτικός γραμματισμός να καλλιεργείται μέσα από πρακτικές δραματοποίησης και παιξίματος ρόλων μέσα στη σχολική τάξη (Schroeter & Wager, 2017). (Djonov & Van Leeuwen, 2013.…”
Section: κριτική προσέγγιση των πολυτροπικών κειμένωνunclassified